The Role of Imagination in Kant`s Theoretical Know ledge (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This research sheds light on the real role imagination plays in building our knowledge besides the two fuclies of sensitivity understanding ,all through finding Coherence and harmony between the two world`s of sensation and understanding via two major roler through which imagination achieves it`s special function of connecting and constituting this making objective knowledge a possibility . An empirical sensuous role in which imagination presents embodiments of things, after uniting sensuous impressions of the faculty of understanding, so it provides it`s characteristics with the appropriate intuitions and makes them conceive things rationally and spontaneously . A creative role in which role imagination practices its most important role of constituting , through providing pure intellectual drawings and plannings ,which introduces for general constituting that understanding characteristics achieves on the level of intellect ,and allows through it for composing objective judgments that accomplish the condition of possible scientific knowledge . The research also demonstrates that word of imagination takes the form of time, that time is homogeneous with intuition because it includes our sensuous embodiments , and it is a general total, and primary role suites all phenomena .